Ekstraksi Ciri Polip dan Pendarahan Berdasarkan Citra Endoskopi Kolorektal - Ummi Athiyah; Izzati Muhimmah; Erlina Marfianti (Jurnal Informatika: Jurnal Pengembangan IT, 2018)
Cancer is one of the main causes of mortality in the world. Colorectal cancer, also known as colon cancer, is a malignant tumor of the colon and rectum that begins with a polyp. Early inspection is needed to prevent and cure of colorectal cancer because in the early stages colorectal cancer showed no symptoms. At this time the development of information technology allows the quick information retrieval from an image. The aim of this research is to produce a preliminary work in the stages of information analyzing on colorectal endoscopic image extraction result in the form of polyp and bleeding by utilizing extraction technique of image information based on shape and texture. This research aimed can be the basis for the development of colorectal cancer detection system framework. The research that has been carried out gives result of characteristics that can be differentiate between colon bleeding, colon polyp, and normal colon conditions, they are aspect ratio, triangle, correlation, and energy.